E-065 Ruptured brain arterio-venous malformations in children and adults: angioarchitectural variations at presentation across the lifespan. (22nd July 2019) - Garzelli, L; Shotar, E; Blauwblomme, T; Sourour, N; Alias, Q; Mathon, B; Kossorotoff, M; Degos, V; Gariel, F; Boddaert, N; Brunelle, F; Meyer, P; et al.
Abstract : Background and Purposes: Intracerebral hemorrhage is the most feared complication of brain arterio-venous malformation bAVM. In patients with ruptured bAVM, the biological and structural angioarchitectural continuum leading to hemorrhage through the lifespan has been scantly reported. In this multicenter retrospective cohort study, we aimed to determine whether ruptured bAVM angioarchitectural features vary across the lifespan. Methods: Pediatric patients with ruptured bAVM referred to a pediatric quaternary care center between 2000 and 2018 and adult patients referred to a tertiary care center between 2003 and 2018 were pooled and retrospectively analyzed. Baseline clinical, demographic and imaging data were either prospectively acquired or retrospectively retrieved from medical charts. Imaging were then retrospectively reviewed for key bAVMs angioarchitectural characteristics, i.e, nidus size, location, Spetzler Grade, venous drainage and arterial or nidal aneurysm. First, demographic, clinical and angioarchitectural characteristics between children and adults were compared. Second, data for pooled sample was analyzed by using Kaplan-Meier survival analyses and log-rank tests, hypothesizing that bAVM and its angioarchitectural features were present at birth: survival started at the time of birth and ended at the date of bAVM rupture. A threshold of p<0.05 was considered significant. Results: A total of 309 patients with ruptured bAVM were included, with 111 children (mean age 9.5 ±3.7) and 198 adults (mean age 43.3 ±15.7), 43% females in both cohorts. Children presented with larger nidal sizes (mean 24.7 mm ±14.3 vs 18.9 ±14.2 p<0.001; Correlation coefficient -0.11 [-0.22—0.03], p=0.04), more frequent central and supra-tentorial location of bAVM (respectively 56.4% vs 22%, p<0.001, and 86% vs 77%, p=0.04), and less frequent flow-related arterial or intranidal aneurysms (respectively 2.8% vs 17% and 13% vs 24%, both p<0.01). Other angioarchitectural features did not differ significantly between cohorts. Using age at diagnosis as a continuous variable, earlier presentation of ruptured bAVM, was associated with central/deep and supra tentorial locations (log rank p<0.01for both) and with deep or mixed venous drainage (log rank p=0.019). On the contrary, Flow related or intra-nidal aneurysms appeared more frequent at older ages (log rank p<0.001), See figure 1. Conclusion: Centrally located bAVM, especially when supra-tentorial and with deep or mixed venous drainage are more frequent in patients with ruptured bAVM early in life. On the contrary, arterial or nidal aneurysm is less frequent in younger patients, possibly indicating that these frailty features develop later. Whether their occurrence in adult unruptured bAVM justify treatment need to be confirmed in prospective studies. Disclosures: L. Garzelli: None. E. Shotar: None. T. Blauwblomme: None. N. Sourour: None. Q. Alias: None. B. Mathon: None. M. Kossorotoff: None. V. Degos: None. F. Gariel: None. N. Boddaert: None. F. Brunelle: None. P. Meyer: None. O. Naggara: None. F. Clarençon: None. G. Boulouis: None.